Prenatal Alcohol Exposure and Metabolic Disorders in Pediatrics: The Role of the Oxidative Stress-A Review of the Literature - Martina Derme; Martina Briante; Mauro Ceccanti; Giuseppe Giannini; Mario Vitali; Marisa Patrizia Messina; Maria Grazia Piccioni; Alessandro Mattia; Simona Nicotera; Alba Crognale (MDPI AG, 2024)
Prenatal alcohol exposure is responsible for increasing chronic disease risk in later life, including obesity and metabolic syndrome. Alcohol drinking may compromise endogenous antioxidant capacity, causing an increase in free radicals and reactive oxygen species in the newborn. Excessive reactive oxygen species could attack the cellular proteins, lipids, and nucleic acids, leading to cellular dysfunction. Moreover, oxidative stress could play a crucial role in the altered synthesis and release of neurotrophins and progressive mitochondrial modifications with uncontrolled apoptosis. This narrative review aims to underline the important role of alcohol abuse in oxidative stress events and consequent metabolic and neurocognitive impairments in children exposed to alcohol during gestational life.